Gendered Narratives in Children’s Literature: Analyzing Femininity and Power - Al-Gailany, Maha M.; Hussein, Abeer Khalaf; Hazem, Ali Hussein (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Children’s literature plays a crucial role in shaping young minds by constructing and representing gender roles and expectations. In classic stories, the male protagonists are usually active, adventurous, and solvers of problems, whereas the female roles are supporting, nurturing, and waiting to be rescued. This study seeks to examine images of femininity and power relations in society dealt with in children’s literature through its female characters’ levels of agency, power, and children-related roles. The data of the study involves selected excerpts from the classic children’s literature “Sindbad, the Sailor’s Seven Voyages” written anonymously in (1835) in “The Arabian Nights’ Entertainments” by Philadelphia/Thomas Wardle. Connell’s (1987) model of power and gender is adopted for the analysis where nine excerpts are randomly selected from the seven voyages stories of Sindbad. Each excerpt is given, then the effects of themes like authority, financial inequality, and social norms on both family and society are reflected along with discussion for each analysis. It is concluded that the traditional children’s literature often reinforces patriarchal norms, particularly in the portrayal of femininity and power dynamics. Female characters are often marginalised and used as tools to maintain male authority, reinforcing traditional gender roles and limiting female agency. Hence, the findings imply that Sindbad the Sailor’s story reflects a world shaped by patriarchal power, with women showing little economic power, not much authority, and being stuck in roles based on traditional gender norms. The conclusion proves the given hypothesis.